NK cell signaling to cytotoxicity - part I - Billadeau, Dan (Henry Stewart Talks, 2010)
NK cell cytotoxicity, Introduction to NK cell activating receptors, Regulation of NK cell cytotoxicity by immunoreceptor tyrosine-based activation motif associated receptors, The downstream targets regulating NK cytolytic activity, PI3K pathway is required for the development of cellular cytotoxicity, LAT/NTAL are required for DAP12-initiated cytotoxicity and production of interferon gamma, PLCγ2 is required for NK cell killing, Vav proteins are linked to NK cell activating receptors and regulate the development of cellular cytotoxicity, Rho family GTP-binding proteins regulate NK cell-mediated cytotoxicity